In a closet hidden : the life and work of Mary E. Wilkins Freeman - Glasser, Leah Blatt, 1951- (Amherst : University of Massachusetts Press, 1996)
"The first literary biography of a much-neglected American writer, this book explores the multiple tensions at the core of Mary E. Wilkins Freeman's life and work. A prolific short story writer and novelist, Freeman (1852-1930) developed a reputation as a local colorist who depicted the peculiarities of her native New England. Yet as Leah Blatt Glasser shows, Freeman was one of the first American authors to write extensively about the relationships women form outside of marriage and motherhood, the role of work in women's lives, the complexity of women's sexuality, and the interior lives of women who rebel rather than conform to patriarchal strictures." "In a Closet Hidden traces Freeman's evolution as a writer, showing how her own inner conflicts repeatedly found expression in her art. As Glasser demonstrates, Freeman's work examined the competing claims of creativity and convention, self-fulfillment and self-sacrifice, spinsterhood and marriage, lesbianism and heterosexuality."--Jacket.
"Nurtured in repression" -- "The art of my work" -- "Sometimes I think I am a monster" -- Sexual politics in Pembroke -- "Savage squaw" and "Fair angel" in Madelon -- "The tenderness of one woman for another" -- "If you don't see the old me" -- Freeman and two New England contemporaries [Sarah Orne Jewett and Charlotte Perkins Gilman].
Includes bibliographical references (pages 233-256) and index.
"Selected bibliography of the works of Mary E. Wilkins Freeman": (pages 257-260).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Freeman, Mary Eleanor Wilkins, -- 1852-1930.; Freeman, Mary Eleanor Wilkins, -- 1852-1930; Freeman, Mary Eleanor Wilkins; Feminism and literature -- New England -- History -- 19th century; Women and literature -- New England -- History -- 19th century; Lesbians' writings, American -- History and criticism; Authors, American -- 19th century -- Biography; Authors, American -- 20th century -- Biography; Sex role in literature; Femmes et littérature -- Nouvelle-Angleterre -- Histoire -- 19e siècle.; Écrits de lesbiennes américains -- Histoire et critique; Écrivains américains -- 19e siècle -- Biographies; Écrivains américains -- 20e siècle -- Biographies; Rôle selon le sexe dans la littérature.; LITERARY CRITICISM -- American -- General; BIOGRAPHY & AUTOBIOGRAPHY / General; Authors, American; Feminism and literature; Lesbians' writings, American; Sex role in literature; Women and literature; New England; Biografie; 1800-1999; Biographies; Criticism, interpretation, etc; History